Prevalence and correlates of beta human papillomavirus detection in fingernail samples from mid-adult women - Rachel L. Winer; Tarik Gheit; Stephen Cherne; John Lin; Joshua E. Stern; Mario Poljak; Qinghua Feng; Massimo Tommasino (Papillomavirus Research, 2018)
Cutaneous human papillomaviruses (HPVs) have not been evaluated in fingernails from healthy individuals. To determine prevalence and correlates of β-HPVs in fingernails from healthy mid-adult women, we tested archived samples collected from 2011 to 2012 using a multiplex PCR combined with Luminex technology for 46 β-HPV genotypes. One hundred thirteen (61.1%) of 185 fingernail samples were positive for β-HPV, and the median number of types detected in positive samples was 2 (interquartile range: 1–4). The most common genotypes detected were HPV-23 (β−2) (13.5%), HPV-38 (β−2) (13.0%), HPV-5 (β−1) (9.2%), HPV-107 (β−2) (8.7%), and HPV-120 (β−2) (8.7%). In multivariate analysis, β-HPV detection was associated with age (prevalence ratio [PR] for women 40–51 years versus 30–39 years = 1.30, 95% CI: 1.05–1.62) and race (PR for non-white versus white race = 0.65, 95% CI: 0.45–0.94). The prevalence of β-HPV in fingernail samples from healthy mid-adult women was similar to the prevalence of β-HPV reported at other cutaneous sites in prior studies. We did not identify any significant health or sexual behavior predictors of β-HPV detection in fingernails. Our results support the hypothesis that fingers may serve as a source of transmission or autoinoculation of cutaneous HPVs to other anatomic sites. Keywords: Fingernails, Women, Beta-HPV, Prevalence, Mid-adult, Risk factor